2020
DOI: 10.3389/fendo.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Related Multifactorial Control of Pituitary Gonadotropin and Growth Hormone in Female Goldfish: Influences of Neuropeptides and Thyroid Hormone

Abstract: Female reproduction is under multifactorial control of brain-pituitary-peripheral origin. The present study provides information on seasonal changes in circulating LH and GH concentrations, as well as transcript levels for a number of genes involved in the regulation of reproduction and growth in female goldfish. We also provide information on the effects of treatments with GnRH and/or GnIH, and their interaction with T3, at three stages of gonadal recrudescence. Maximum basal concentration of LH was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 122 publications
5
18
0
Order By: Relevance
“…In general, single GnRH injection inhibited metabolic pathways related to reproductive processes, whereas double injection enhanced the pathways related to reproduction at mid recrudescence (Table 4). This is consistent with the observation that single GnRH injection decreased Vtg and IGF-I mRNA levels, which was increased following double injection with GnRH in goldfish at mid recrudescence (Ma et al, 2020b). In the present study, double injection with GnRH also enhanced taurine and hypotaurine metabolism (Figure 8; Table 4).…”
Section: Mid Recrudescencesupporting
confidence: 92%
See 3 more Smart Citations
“…In general, single GnRH injection inhibited metabolic pathways related to reproductive processes, whereas double injection enhanced the pathways related to reproduction at mid recrudescence (Table 4). This is consistent with the observation that single GnRH injection decreased Vtg and IGF-I mRNA levels, which was increased following double injection with GnRH in goldfish at mid recrudescence (Ma et al, 2020b). In the present study, double injection with GnRH also enhanced taurine and hypotaurine metabolism (Figure 8; Table 4).…”
Section: Mid Recrudescencesupporting
confidence: 92%
“…The observed higher concentration of tyrosine in regressed, compared to mid and late recrudescence, is correlated with higher circulating thyroid hormones (T3 and T4) in the regressed goldfish (Sohn et al, 1999). Our results combined with observed higher thyroid hormone receptor (TRβ) mRNA level in the regressed female goldfish liver (Ma et al, 2020b), provide further support for the hypothesis that thyroid hormones are essential components of growth response during the regressed gonadal phase in fish. It should be noted that the role of thyroid hormones in the control of growth is widely recognized (Cabello and Wrutniak, 1989;Nelson and Habibi, 2009).…”
Section: Regressed Gonadal Phase Is Characterized By Growth-promoting...supporting
confidence: 79%
See 2 more Smart Citations
“…Studies have shown that THs may act at the pituitary level to inhibit gonadotropin secretion. Hypothyroid conditions decrease pituitary LH immunoreactivity and LH circulating levels in male recrudescent air-breathing catfish ( 249 ), and, in recrudescent goldfish, administration of T 3 decreases pituitary LH mRNA expression in males ( 251 ) and attenuates GnRH-induced LH secretion in females ( 252 ).…”
Section: Reproductionmentioning
confidence: 99%